Answer:
![40x^{2} y^{4} -70x^{2} y^{2} +90xy^{3}](https://tex.z-dn.net/?f=40x%5E%7B2%7D%20y%5E%7B4%7D%20-70x%5E%7B2%7D%20y%5E%7B2%7D%20%2B90xy%5E%7B3%7D)
Step-by-step explanation:
1. 10xy · 4xy^3 = ![40x^2y^4](https://tex.z-dn.net/?f=40x%5E2y%5E4)
2. 10xy · -7xy = ![-70x^{2} y^{2}](https://tex.z-dn.net/?f=-70x%5E%7B2%7D%20y%5E%7B2%7D)
3. 10xy · 9y^2 =
Final step: add up all of those values together to make an equation!
Answer:
![90xy^3](https://tex.z-dn.net/?f=90xy%5E3)
Final Answer: ![40x^2y^4-70x^2y^2+90xy^3](https://tex.z-dn.net/?f=40x%5E2y%5E4-70x%5E2y%5E2%2B90xy%5E3)
Answer:
D In step 3
Step-by-step explanation:
Given polynomial: x² - 2x - 15 = 0
Step 1: factor the polynomial ⇒ (x + 3)(x - 5) = 0
Step 2: x + 3 = 0 and x - 5 = 0
Step 3: x = -3 and x = 5
x - 5 = 0
Add 5 to both sides:
⇒ x - 5 + 5 = 0 + 5
⇒ x = 5
Answer: 152 I think
Step-by-step explanation: